Efektivitas Model PBL Berbantuan Electronic Portfolio Berbasis Web Terhadap Ownership of Learning, Keterampilan Berpikir Kritis, Keterampilan Pemecahan Masalah, dan Hasil Belajar Kognitif Siswa - Mutsaqqofa, Amna Roisah; Susilo, Herawati; Prabaningtyas, Sitoresmi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This research aims to determine the effectiveness of the web-based electronic portfolio-assisted PBL model on ownership of learning, critical thinking skills, problem-solving skills, and cognitive learning outcomes. The type of this research is pre-experimental with a one-group pretest-posttest design involving 36 XI IPA students at SMAN 7 Malang.The measurement instruments used include a learning ownership questionnaire, a critical thinking skills test in essay form, a problem-solving skills test in essay form, and a cognitive learning outcomes test in multiple-choice form. Data analysis using the N-gain test to measure the overall effectiveness of learning by looking at the improvement in student scores from pretest and posttest results. The research results show the average N-gain score for ownership of learning (N-gain = 0.3 low), critical thinking skills (N-gain = 0.7 moderate), problem-solving skills (N-gain = 0.6, moderate), and cognitive learning outcomes (N-gain = 0.4 moderate).Thus, it shows that the web-based electronic portfolio-assisted PBL model is an effective teaching strategy to enhance students' ownership of learning, critical thinking skills, problem-solving skills, and cognitive learning outcomes in the learning process.